(untitled) (Revista Inclusiones, 2020)
In the context of integration and globalization of the world economy, the strategic goal of the higher vocational school is to ensure the advanced development of the scientific and technological potential of society. However, there is a lack of understanding of the role of scientific activities of the university in the implementation of educational programs. The purpose of the present article is to identify the essence of the scientific work of the chair as an integrative component of the scientific activity of the university and to justify the method of its objective assessment.